Advancing a social identity perspective on interoperability in the emergency services: Evidence from the Pandemic Multi-Agency Response Teams during the UK COVID-19 response. (July 2022) - Davidson, Louise; Carter, Holly; Drury, John; Amlôt, Richard; Haslam, S. Alexander
Abstract: Previous research shows there are persistent challenges with multi-agency response centring on problems of communication and coordination. The Social Identity Approach provides an important psychological framework for analysing relations within and between groups which can be used to understand why challenges in multi-agency response occur, and what can be done to prevent them re-occurring in the future. To explore this issue, we conducted semi-structured interviews with 14 responders from the Police, and Fire and Rescue Services who were involved in Pandemic Multi-Agency Response Teams (PMART) during the initial months of the COVID-19. These teams responded to suspected COVID-19 deaths in the community. Interviews were analysed using thematic analysis. Results show that responders appeared to share the pre-existing superordinate identity of all being members of the blue-light service . This identity was made salient as a result of responders experiencing positive contact with each other. Responders also shared the situational superordinate identity of PMART which was both created, and then made salient, through positive contact with each other, as well as responders sharing difficult experiences. At the same time though, structural factors such as inequalities in building access and different shift patterns increased the salience of sub-group identities in ways that created conflict between these identities, as well as operational challenges for joint working. This research advances our understanding of multi-agency working from a social identity perspective by providing evidence of a shared social identity at an operational level of emergency response. Practical implications of this research are discussed.